Is China's low fertility rate caused by the population control policy? - Liu Qiang; Fernando Rios-Avila; Jiqin Han (Levy Economics Institute of Bard College, 2020)
Whether China's low fertility rate is the consequence of the country's strict population control policy is a puzzling question. This paper attempts to disentangle the Chinese population control policy's impacts on the fertility rate from socioeconomic factors using the synthetic control method proposed by Abadie and Gardeazabal (2003). The results indicate that the population control policy significantly decreased China's birth rate after the "Later, Longer, and Fewer" policy came into force, but had little effect on the birth rate in the long run. We estimate that between 164.2 million and 268.3 million prevented births from 1971 to 2016 can be attributed to the Chinese population control policy. In addition, we implement a placebo study to check the validity of the method and confirm the robustness of the paper's conclusions.
Keywords: C21; J13; Q56; 330; Birth Rate; China; Population Control Policy; Synthetic Control Method; Placebo Study